IECON 2011 - 37th Annual Conference of the IEEE Industrial Electronics Society 2011
DOI: 10.1109/iecon.2011.6119384
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear FOPDT model identification for the superheat dynamic in a refrigeration system

Abstract: An on-line nonlinear FOPDT system identification method is proposed and applied to model the superheat dynamic in a supermarket refrigeration system. The considered nonlinear FOPDT model is an extension of the standard FOPDT model by means that its parameters are time dependent. After the considered system is discretized, the nonlinear FOPDT identification problem is formulated as a Mixed Integer Non-Linear Programming problem, and then an identification algorithm is proposed by combining the Branch-and-Bound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…We also observed that the estimation of varying time-delay can result in a nonconvex optimization problem (Yang and Sun (2011)). The simplest and straightforward way to estimate the inputoutput delay of a LTI system is to use the cross-correlation analysis (Richard (2003)), or by some experimental approaches (Åström and Hägglund (1995)).…”
Section: On-line Miso Tv-fopdt Identificationmentioning
confidence: 99%
See 4 more Smart Citations
“…We also observed that the estimation of varying time-delay can result in a nonconvex optimization problem (Yang and Sun (2011)). The simplest and straightforward way to estimate the inputoutput delay of a LTI system is to use the cross-correlation analysis (Richard (2003)), or by some experimental approaches (Åström and Hägglund (1995)).…”
Section: On-line Miso Tv-fopdt Identificationmentioning
confidence: 99%
“…and τ k are called as the kth-step sampled system gains and time constant, respectively (Yang and Sun (2011) (2) and (3), correspondingly. The former ones are piecewise-constant (i.e., constant during every sampling period) time functions, while the latter ones are continuously-varying time functions.…”
Section: Discretizationmentioning
confidence: 99%
See 3 more Smart Citations